THE REBIRTH OF THE LONG-REPEALED ARTICLES ON INSULT AGAINST PRESIDENT IN INDONESIA’S NEW CRIMINAL CODE - An Nisaa Athirah; Muhamad Dzikra Dandiansyah; Muhammad Keenan Abiyyu (Faculty of Law Atma Jaya Yogyakarta University, 2025)
The current Indonesian Criminal Code, rooted in the 1915 Dutch Colonial Criminal Code, includes provisions that penalize insults against the president and vice president. Historically, Articles 134, 136 bis, and 137 were utilized to suppress freedom of speech. In 2006, these articles were deemed unconstitutional by the Constitutional Court, signaling a commitment to democratic values. However, the recent reintroduction of similar provisions through Article 218, 219, and 220 of Law No. 1/2023 raises critical concerns about the erosion of democracy and potential violations of constitutional rights, particularly freedom of speech as protected by Article 28E of the Constitution. This study formulates the problem of how these legal changes impact Indonesia’s democratic principles and human rights. Employing a normative legal research methodology, it analyzes relevant laws, including Articles 218, 219, and 220 of the new Criminal Code, alongside previous articles. Furthermore, a comparative study is conducted by examining similar regulations in Turkey and the United States to evaluate different legal frameworks in handling freedom of speech. The findings indicate that reintroducing these provisions, despite the court's ruling, reflects authoritarian tendencies detrimental to Indonesia's democratic progress. This research highlights the urgent need for vigilance in protecting democratic norms and human rights in the face of legislative shifts that threaten dissent and criticism, and offers comparative insights that may guide future legal reform.